Audience Reception of Othman Alibrahim’s Kun Fayakun: A Reader-Response Study - Rizki Rinaldi; Ahmad Fauzan (Jurnal Bahasa dan Sastra Pusaka Cendekia, 2026)
This study examines how digital audiences construct meaning around Othman Alibrahim’s Arabic acapella nasheed Kun Fayakun through Wolfgang Iser’s reader-response framework. Using a qualitative interpretive design, the study analyzes fifteen public YouTube comments documented from the performance’s comment section and selected purposively because they directly address the singer, the nasheed’s spiritual message, or affective-symbolic reactions. The comments were anonymized and coded according to response focus, shared repertoire, textual indeterminacy, and audience concretization. The findings identify three interconnected reception patterns. First, aesthetic-performative responses foreground vocal clarity, acapella delivery, and the singer’s expressive quality. Second, spiritual-textual responses interpret the nasheed through an Islamic repertoire of divine power, supplication, hope, and healing. Third, symbolic-affective responses use emojis and brief expressions to condense admiration, grief, serenity, and spiritual comfort. The study argues that YouTube comments make visible forms of concretization that remain largely implicit in conventional literary reading. It extends Iser’s framework to digital musical reception while emphasizing that a small purposive comment corpus cannot represent the entire audience.   Penelitian ini mengkaji bagaimana audiens digital membangun makna terhadap nasyid akapela Arab Kun Fayakun karya Othman Alibrahim melalui kerangka respons pembaca Wolfgang Iser. Penelitian menggunakan desain kualitatif interpretatif dengan menganalisis lima belas komentar publik YouTube yang didokumentasikan dari kolom komentar pertunjukan dan dipilih secara purposif karena secara langsung membahas penyanyi, pesan spiritual nasyid, atau respons afektif-simbolik. Identitas pengguna dianonimkan dan data dikodekan berdasarkan fokus respons, repertoar bersama, ketaktertentuan teks, dan konkretisasi audiens. Hasil penelitian menunjukkan tiga pola resepsi yang saling berkaitan. Pertama, respons estetis-performatif menonjolkan kejernihan vokal, penyajian akapela, dan ekspresivitas penyanyi. Kedua, respons spiritual-tekstual memaknai nasyid melalui repertoar Islam tentang kekuasaan Ilahi, doa, harapan, dan penyembuhan. Ketiga, respons simbolik-afektif menggunakan emoji serta ungkapan singkat untuk memadatkan kekaguman, kesedihan, ketenangan, dan kenyamanan spiritual. Penelitian ini menunjukkan bahwa komentar YouTube dapat memperlihatkan proses konkretisasi makna yang sering tidak terlihat dalam praktik pembacaan konvensional. Kajian ini memperluas penerapan teori Iser pada resepsi musik digital, sekaligus menegaskan bahwa korpus komentar purposif yang kecil tidak dapat mewakili seluruh audiens.